The appraisement of adaptive ability of promising lines of soybean in the conditions of the Samara region - A. I. Katyuk; E. V. Zuev; V. V. Zubkov (Зерновое хозяйство России)
The appraisement of adaptive ability of promising lines of soybean in the conditions of the Samara region In 2009-2014 in Samara RIA several promising lines and varieties of soybean were studied on grain productivity. the purpose of the research is to identify genotypes adapted to the conditions of Middle Povolzhie. The studied years differed in heat and moisture supply in the vegetation period of crops that allowed assessing the variety samples according to the parameters of adaptive ability. The adaptive ability has been valued according to well-known statistic parameters, calculated on grain productivity. The lines ‘05-117’, ‘05-137’, ‘S04124’, ‘12108’, ‘06-143’ and ‘LS4М’, developed by the Samara RIA and the Ershosky OSOZ, have been introduced into the trial. The varieties ‘Samer 1’, ‘Samer 2’ and ‘Samer 3’, included into the Register of Breeding Achievements were taken as standard ones. The conducted research determined a mixed reaction of the lines on agroclimatic conditions. During five years of testing the line ‘05-117’ produced the largest yields on average and exceeded the best standard variety ‘Samer 2’ on 6.0%. The assessment of the lines according to the maximum of grain productivity and its stable formation during the years and parameters of its adaptive ability gave the opportunity to find lines ‘05-137’, ‘12108’, ‘06-143’ and ‘05-117’ adapted to the conditions of the Middle Volga region. In the favourable climatic year the line ’05-117’ showed the best productivity of grain. Its testing in KFH IP “E.P. Tsirulev’ on the intensive background confirmed the responsiveness of the line on the factors of intensification (irrigation, fertilizing).